Vapochromic properties versus metal ion coordination of β-bispyrazolato–copper(ii) coordination polymers: a first-principles investigation. Issue 2 (2nd October 2014) - Casarin, Maurizio; Forrer, Daniel; Pandolfo, Luciano; Pettinari, Claudio; Vittadini, Andrea
Abstract : Vapochromic properties of Cu(ii ) coordination polymers are explained on the basis of first principles calculations. Abstract : A series of monoadducts of the β-bispyrazolato–copper(ii ) one-dimensional coordination polymer is investigated with plane-wave density functional theory–dispersive interactions (DFT-D) calculations. It was found that weak Lewis bases, such as H2 O and CH3 OH, prefer a symmetric bridging coordination to the Cu(ii ) ions, which in turn assume a highly distorted 4 + 2 octahedral configuration. Stronger Lewis bases, namely, NH3 and pyridine, prefer instead to bind to a single Cu(ii ) ion, which adopts a 5-fold coordination in a square-pyramidal environment. A semi-bridging coordination, corresponding to a 5 + 1 distorted octahedral Cu(ii ) environment, is finally predicted for molecules of intermediate Lewis basicity, such as CH3 CN. The soundness of these results is corroborated by a good correlation found between the theoretical coordination number of the Cu(ii ) ions, the computed spin-down fundamental band gap, and the experimentally observed vapochromic effects.